Diagnostic Accuracy of Optical Coherence Tomography to Detect Cystoid Macular Edema (CME) In Patients with Diabetes Mellitus (DM) Taking Fundus Fluorescein Angiography (FFA) As Gold Standard: Diagnostic Accuracy of Tomography in Diabetes Mellitus - Nawaz, Atia; Aleem, Nouman; Waheed, Mustafa Khalid; Ahmad, Muhammad Abrar; Akhtar, Fahd Kamal; Siddiq, Saqib (Pakistan Journal of Health Sciences, 2025)
Macular thickening, known as Cystoid Macular Edema (CME), is brought on by fluid buildup in the inner nuclear and outer plexiform layers of the retina as a result of leaking from peri-foveal retinal capillaries. Objective: To determine the OCT’s ability to identify cystoid macular edema in individuals with diabetes mellitus, compared to the gold standard of fundus fluorescein angiography. Methods: The Lahore General Hospital’s Ophthalmology Outpatient Clinic served as the study’s setting. From the Outpatient Department, 143 patients who met the inclusion criteria were randomly selected. Informed consent was obtained from patients before imaging. An indirect biomicroscope was used to evaluate all of the subjects. After completing fundus fluorescein angiography and optical coherence tomography, was diagnosed with cystoid macular edema according to the standardized criteria. A data collection proforma was developed. IBM SPSS version 25.0 was used to analyze the data. Results: In this study, 76 males (53.1%) and 67 females (46.9%) participated. The average age was 47.7 ± 10.3 years and diabetes duration was 5.4 ± 2.9 years. Optical Coherence Tomography (OCT) showed a sensitivity of 88.3%, specificity of 38.5%, PPV of 93.3%, NPV of 25.0%, and an overall accuracy of 84.6% compared to Fluorescein Angiography (FFA) in detecting cystoid macular edema. Conclusions: Diagnosing DME with OCT and FFA is very successful, it ensures early detection and treatment. For Diabetic Mellitus (DM) patients to avoid eyesight loss, accurate and easily accessible diagnostic strategies are essential.